New species and record of Gastrochilus (Orchidaceae, Aeridinae) from China and Laos - Liu, Qiang; Wu, Xun-Feng; Zhou, Shi-Shun; Li, Jian-Wu; Jin, Xiao-Hua (Phytotaxa, 2023)
Four new species of Gastrochilus (Vandeae, Orchidaceae) — G. menglaensis, G. tsii, G. wenshanensis and G. labrosus—are here described and illustrated, based on materials collected from China and Laos. Additionally, Gastrochilus minutiflorus is for the first time recorded in China and G. brevifimbriatus is reduced to a synonym of G. fargesii.